2003
DOI: 10.1051/0004-6361:20021609
|View full text |Cite
|
Sign up to set email alerts
|

The 0.4-$M_{\odot}$ eclipsing binary CU Cancri

Abstract: Abstract. Photometric observations in the R and I bands of the detached M-type double-lined eclipsing binary CU Cnc have been acquired and analysed. The photometric elements obtained from the analysis of the light curves have been combined with an existing spectroscopic solution to yield high-precision (errors < ∼ 2%) absolute dimensions:0052 R , and R B = 0.3908 ± 0.0094 R . The mean effective temperature of the system has been estimated to be T eff = 3140 ± 150 K by comparing multi-band photometry (optical a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
197
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(224 citation statements)
references
References 48 publications
24
197
3
Order By: Relevance
“…Since the properties of the more massive primary star appear to be well reproduced by the models (as expected from previous experience; see Andersen 2003), suspicion falls on our theoretical understanding of stars under a solar mass. Similar evidence has been presented over the last several years (e.g., Popper 1997;Clausen et al 1999a;Torres & Ribas 2002;Ribas 2003;Dawson & De Robertis 2004;López-Morales & Ribas 2005), but in fact indications go as far back as the work by Hoxie (1973), Lacy (1977), and others. All of these studies have shown that theoretical calculations for stars less massive than the Sun tend to underestimate the radius by as much as 10%-20%.…”
Section: Comparison With Evolutionary Modelssupporting
confidence: 80%
“…Since the properties of the more massive primary star appear to be well reproduced by the models (as expected from previous experience; see Andersen 2003), suspicion falls on our theoretical understanding of stars under a solar mass. Similar evidence has been presented over the last several years (e.g., Popper 1997;Clausen et al 1999a;Torres & Ribas 2002;Ribas 2003;Dawson & De Robertis 2004;López-Morales & Ribas 2005), but in fact indications go as far back as the work by Hoxie (1973), Lacy (1977), and others. All of these studies have shown that theoretical calculations for stars less massive than the Sun tend to underestimate the radius by as much as 10%-20%.…”
Section: Comparison With Evolutionary Modelssupporting
confidence: 80%
“…However, radii of single inactive M dwarfs measured by interferometry are in excellent agreement with models from Baraffe et al (1998). Thus, the discrepancies pointed out by Torres & Ribas (2002) and Ribas (2003) only concern fast-rotating stars, confirming that rotation strongly affects the internal structure of those objects. …”
Section: Activitymentioning
confidence: 72%
“…While these three determinations are not completely independent, their consistency despite the widely different ingredients reinforces our conclusion that the model ΔT eff is at least ∼ 250 K too small. Stellar evolution models have been shown previously to overestimate the effective temperatures of low-mass stars in eclipsing binaries by up to ∼ 200 K (e.g., Torres & Ribas 2002;Ribas 2003). The study of V1061 Cyg by Torres et al (2006) suggested that the problem is not confined to M dwarfs, but extends up to masses almost as large as that of the Sun (0.93 M in the case of V1061 Cyg B).…”
Section: Discussionmentioning
confidence: 99%